A Rare Case of Pulmonary Leiomyosarcoma - Jialin He; Yun Tang; Fei Zhao; Bo Zheng; Shihai Tang; Juan Gong; Li Wang; Yang Zhou (Acta Medica Indonesiana)
Leiomyosarcoma commonly occurs in the abdomen, retroperitoneum, large blood vessels, and uterus[1]. Cardiac leiomyosarcoma is a rare and highly aggressive sarcoma. We reported a case of a 63-year-old male with pulmonary artery leiomyosarcoma. Transthoracic echocardiography showed a large 4.4×2.3 cm hypoechoic mass in the right ventricular outflow tract and pulmonary artery. Computed tomography pulmonary angiography showed a filling defect in a similar location. The initial impression was PE, but a tumor was not ruled out. An emergency surgery was performed due to progressively worse chest distress and dyspnea. A yellow mass that had adhered to the ventricular septum and pulmonary artery wall was detected to be compressing the pulmonary valve. Immunohistochemistry confirmed tumor cells positive staining for Desmin and smooth muscle actin and negative staining for S-100, CD34, myogenin, or myoglobin, and KI67(+)80%, indicating leiomyosarcoma. Pulmonary leiomyosarcoma showed a side-inserted heart chamber filling defect in CTA and should be excised when the patient suddenly deteriorated.